Neutrophil Extracellular Traps Are Elevated in Patients with Pneumonia-related Acute Respiratory Distress Syndrome. (April 2019) - Bendib, Inès; de Chaisemartin, Luc; Granger, Vanessa; Schlemmer, Frédéric; Maitre, Bernard; Hüe, Sophie; Surenaud, Mathieu; Beldi-Ferchiou, Asma; Carteaux, Guillaume; Razazi, Keyvan; Chollet-Martin, Sylvie; Mekontso Dessap, Armand; et al.
Editor's Perspective: What We Already Know about This Topic: Neutrophil extracellular traps are increasingly recognized as pathogenic in acute injury, but their role in sepsis-related acute respiratory distress syndrome is unknown What This Article Tells Us That Is New: In 35 patients with acute respiratory distress syndrome secondary to pneumonia, neutrophil extracellular traps were elevated in the blood and bronchoalveolar fluid, and associated with interleukin-8 and neutrophil levels; however, higher ( vs . lower) levels of neutrophil extracellular traps were not associated with mortality or duration of mechanical ventilation Background: Neutrophil extracellular traps have been associated with tissue damage. Whether these are involved in the pathogenesis of human acute respiratory distress syndrome (ARDS) and could be a potential therapeutic target is unknown. The authors quantified bronchoalveolar and blood neutrophil extracellular traps in patients with pneumonia-related ARDS and assessed their relationship with ventilator-free days. Methods: Immunocompetent patients with pneumonia and moderate or severe ARDS (n = 35) and controls (n = 4) were included in a prospective monocentric study. Neutrophil extracellular trap concentrations were quantified (as DNA–myeloperoxidase complexes) in bronchoalveolar lavage fluid and serum by enzyme-linked immunosorbent assay. The relationship between bronchoalveolar lavage neutrophil extracellular trap concentrations and the primary clinical endpoint ( i.e., the number of live ventilator-free days at day 28) was assessed using linear regression analyses. Results: There was no significant relationship between bronchoalveolar lavage neutrophil extracellular trap concentrations and ventilator-free days by multiple regression analysis (β coefficient = 2.40; 95% CI, −2.13 to 6.92; P = 0.288). Neutrophil extracellular trap concentrations were significantly higher in bronchoalveolar lavage than in blood of ARDS patients (median [first to third quartiles]:154 [74 to 1, 000] vs . 26 [4 to 68] arbitrary units, difference: −94; 95% CI, −341 to −57; P < 0.0001). Bronchoalveolar concentrations of patients were higher than those of controls (154 [74 to 1, 000] vs. 4 [4 to 4] arbitrary units, difference: −150; 95% CI, −996 to −64; P < 0.001) and associated with bronchoalveolar interleukin-8 (Spearman's ρ = 0.42; P = 0.012) and neutrophil concentrations (ρ = 0.57; P < 0.0001). Intensive care unit mortality (12%, n = 2 of 17 vs . 17%, n = 3 of 18; P > 0.99) and the number of ventilator-free days at day 28 (22 [14 to 25] vs . 14 [0 to 21] days; difference: −5; 95% CI, −15 to 0; P = 0.066) did not significantly differ between patients with higher (n = 17) versus lower (n = 18) bronchoalveolar neutrophil extracellular trap concentrations. Conclusions: Bronchoalveolar neutrophil extracellular trap concentration was not significantly associated with mechanical ventilation duration in pneumonia-related ARDS. Abstract : In 35 patients with acute respiratory distress syndrome secondary to pneumonia, neutrophil extracellular traps were elevated in the blood and bronchoalveolar fluid, and associated with interleukin-8 and neutrophil levels; however, higher ( vs . lower) levels of neutrophil extracellular traps were not associated with mortality or duration of mechanical ventilation.Supplemental Digital Content is available in the text.